Pediatric septoplasty: benefits, challenges, and clinical recommendations - comprehensive review of Young ESPO - Zieliński, Jakub; Costa, Sara; Cherkes, Maryana; Glibbery, Natalia; Kovács, Petra; Mitrea-Sirețeanu, Luiza; Ciller, Marek; Yılmaz Topçuoğlu, Miray-Su (Journal of Clinical Medicine, 2025)
This comprehensive review examines the role of septoplasty in the pediatric population, emphasizing its therapeutic significance in relieving nasal obstruction and facilitating normal craniofacial growth. Despite the evident advantages of septoplasty, its application in young patients remains a subject of ongoing debate. This issue is primarily characterized by concerns regarding the still-developing immaturity of nasal cartilage, potential intraoperative and postoperative risks, and the current absence of robust data on long-term outcomes following septoplasty. Common complications such as bleeding, septal perforation, saddle nose deformity, and persistent nasal obstruction are reported in the literature; however, many studies lack long-term follow-up data on the incidence of these adverse events and revision rates, which may be higher compared to adult populations, often leading to the need for secondary surgical interventions. Strict inclusion criteria and comprehensive patient selection are paramount to maximize therapeutic success while minimizing complications. Current evidence suggests that appropriately indicated septoplasty can improve airway patency, support optimal facial development, and reduce the risk of secondary sinonasal pathology. There is a significant necessity for additional prospective, large-scale studies to establish standardized therapeutic guidelines and management strategies for this specific population, thereby ensuring effective and evidence-based pediatric otolaryngologic care.
Veröffentlicht: 6. August 2025
Gesehen am 16.01.2026